Long-Run Effects of Democracy on Income Inequality : Evidence from Repeated Cross-Sections - Balcazar, Carlos Felipe (World Bank Group, Washington, DC, 2015)
This paper assesses the link between democracy and inequality. Inequality is measured at the cohort level with pseudo-panel data built from nine Latin American countries' household surveys (1995-2009, biannual). Democracy is measured as a stock during long periods of time both before and after each cohort's year of birth. The paper presents evidence that long-run historical patterns in the degree of democracy relate to income inequality. However, this relationship is non-monotonic: inequality first increases with the stock of democracy before falling. The paper also presents evidence that education may be a mechanism explaining this result.